Optical normalized microscale for optical total recursion electromagnetic flux on Heisenberg space S-H(2) - Körpınar, Talat; Körpınar, Zeliha (Springer, 2022)
In this article, we construct a new design for optical spherical Heisenberg total recursion flux with a normalized microscale in spherical Heisenberg space. Moreover, we demonstrate spherical Heisenberg normalized microscale by Heisenberg recursion operator for some magnetic fibers. Thus, we obtain optical spherical Heisenberg ferromagnetic recursion flux by using optical spherical Heisenberg ferromagnetic normalized microscale in spherical Heisenberg space.
Keywords: Optical frame; Optical spherical Heisenberg total recursion flux; Heisenberg ferromagnetic model; Heisenberg normalized microscale; Nonlocal Elasticity; Vibration Analysis; Equation; Phase; Soliton; Propagation; Combustion; Stability; Mechanics; Evolution